Thermoset plastics product recycling - Mokhtar, Munirah; Ali, Nora'aini (Faculty of Chemical & Natural Resources Engineering, 1995)
Recycling thermoset products is economically sensible as it reduces wastage of precious resources and re-claims valuable energy. The aim of this paper is therefore to briefly review some of the alternatives possible for the recycling of thermostat products.